2013
DOI: 10.21101/cejph.a3750
|View full text |Cite
|
Sign up to set email alerts
|

Pediculosis Capitis: Prevalence and Its Associated Factors in Primary Schoolchildren Living in Rural and Urban Areas in Kaiseri, Turkey

Abstract: Objective: The aim of this study was to investigate the prevalence and risk factors of pediculosis capitis in schoolchildren living in rural and urban areas in Kayseri, a city located in central Anatolia in Turkey.Methods: This cross-sectional school-based study was performed in 24 randomly selected public schools. A total of 8,122 schoolchildren aged 5-16 years, from kindergarten to eighth grade, were examined for the presence of pediculosis capitis. A child was defined as being infested by the presence of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
24
2
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 18 publications
10
24
2
4
Order By: Relevance
“…This is because head lice infestation may be transmitted by sharing infested tools, which is more in agreement with result of this study. Studies from Turkey and Jordan proposed that a significant association between family income and prevalence rate of head lice (AlBashtawy and Hasna, 2012; Gulgun et al, 2013). Our finding is an agreement with them.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is because head lice infestation may be transmitted by sharing infested tools, which is more in agreement with result of this study. Studies from Turkey and Jordan proposed that a significant association between family income and prevalence rate of head lice (AlBashtawy and Hasna, 2012; Gulgun et al, 2013). Our finding is an agreement with them.…”
Section: Discussionsupporting
confidence: 92%
“…This is because mothers, who have a high level of education will have more knowledge about head lice due to their social communication (Toloza et al, 2009;Moradi et al, 2009). The infect of socioeconomic status upon the prevalence rate found in this study support with other studies (Toloza et al, 2009;Moradi et al, 2009;AlBashtawy and Hasna, 2012;Vahabi et al, 2012;Gulgun et al, 2013). In spite of that, it is disagreement with Sim et al (2011) and Tappeh et al (2012), who found no significant relationship between parent's education and infestation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…15,16 Other studies also established the same result; in Turkey by (9.7 urban and 20% rural); in Jordan by (23.5 and 31.2%); in Iran by (0.66 and 1.66%) and in Yemen by (20.6%). [17][18][19][20] The rate of infestation in Egypt was reported as 16.7% by 26.6% in Jordan and 13.5% in Iraq. 10,18,21 In Turkey the rates ranged from 0.54 to 29.4% with an average rate of 10.16% and the rate was found to be 48% in India among children, Worldwide, in Europe prevalence varied from 0.48% to 22.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable available data demonstrate differences between males and females in either or both the prevalence and severity of infection within examples of the Protozoa, Trematoda, Cestoda, Nematoda, and Arthropoda (Alexander and Stimson 1988;Roberts et al 1996Gulgun et al 2013). Some of these differences can be explained by differences in the behaviors between the sexes including occupation and social and cultural practices.…”
Section: Introductionmentioning
confidence: 99%